Tuning the lateral response of unbonded fiber reinforced elastomeric isolators (U-FREIs) through horizontal holes: Experimental and numerical findings. (1st June 2022) - Galano, Simone; Calabrese, Andrea; Losanno, Daniele; Serino, Giorgio; Strano, Salvatore
Highlights: The lateral response of U-FREIs with modified geometries under combined vertical and horizontal action has been investigated through experimental tests. The effect of the modification on the lateral response of U-FREIs with different geometries and horizontal holes patterns is studied. Trends of secant and tangent lateral stiffness of modified U-FREIs are provided for different geometries. Finite Element Analysis of holed U-FREIs are developed and compared with experimental results. Considerations on internal stress distribution in modified U-FREIs are provided to shed light over the improved mechanical behavior. Abstract: Fiber-Reinforced Elastomeric Isolators (FREIs) are elastomeric devices introduced as a low-cost alternative to the well-known Steel-Reinforced Elastomeric Isolators (SREIs). As common in rubber-based devices, the application of FREIs to lightweight structures is challenging as slender bearings tend to be unstable under large horizontal displacements. This paper discusses the effects of a simple modification, consisting of drilled horizontal holes through the elastomeric layers of the bearings, on the lateral response of FREIs. A desirable hardening response and a stability range up to 100% of shear strain has been obtained on modified bearings. This result has been confirmed by experimental tests and finite element analyses. Findings of this work show how the proposed modification allows (i) to reduce the horizontal stiffness of FREIs, (ii) to increase the stable range of lateral deformations of the devices and (iii) to obtain a desired hardening behavior under large horizontal displacements without instability.